Antagonism by dibutyryl adenosine cyclic 3',5'-monophosphate and testololactone of concanavalin A capping (The Rockefeller University Press, 1975)
Exposure of CHO-K1 cells in vitro to dibutyryl adenosine cyclic 3',5'- monophosphate (DBcAMP) plus testololactone produces a rapid, reversible antagonism of ligand-induced collection of initially dispersed concanavalin A (Con A) binding sites into a caplike mass. Morphologically, as Con A capping occurs, the cells become less spread and then round completely. With prolonged Con A exposure, cells cultured in either the absence or the presence of DBcAMP plus testololactone cap and round. Capping is blocked by cold treatment and respiratory inhibitors. Colcemid at concentrations greater than 1 muM promotes both Con A capping and cell rounding. Cytochalasin B at similar concentrations inhibits both capping and cell rounding. Treatment of cells with Con A has little effect on intracellular cAMP concentration. Possible mechanisms by which cAMP may modulate the movement of Con A binding sites are discussed.